(untitled) (Latakia University Journal -Basic Sciences Series, 2016)
تمّ في هذا العمل استخدام حجيرة تأين و وسط قياس متجانس، ( المجسّم المائي ) لقياس الجرعة الإشعاعية الناتجة عن حزمة الفوتونات الصّادرة عن المسّرع الخطي الطبي Varian Clinic 23ix، ثم تمّت مقارنة تلك القياسات التجريبية مع حسابات نظريةPBC(Pencil Beam Convolution) المستخدمة في نظام تخطيط المعالجة TPS . تُشير نتائج المقارنة إلى توافق جيّد ومقبول بالمقارنة مع القيم المسموحة للمقادير المعتبرة كالنسبة المئوية للجرعة بالعمق، والجرعة السطحية ،( جرعة الدخول )، قيم التناظر، التسطح والظليل الإشعاعي لحزم الطاقة المستخدمة . In this work, we have used an ionization chamber and a homogeneous medium (water phantom) for measuring the radiant dose of the photons beam that produced by the medical linear accelerator Varian Clinic 23ix, then we have compared the experimental measurement with PBC(Pencil Beam Convolution)theoretical calculations that used in treatment planning system (TPS) . The comparison results refers to good and acceptable agreement by compare with the allowable values of the considered quantities such as percent depth dose, surface dose (entrance dose) and values of the symmetry, flatness and penumbra for the used energy beams .